Potential Of Soil Liquefaction At Perlis, Malaysia Region - Mohamad Amzar Mhd Nasir. (School of Environmental Engineering, University Malaysia Perlis, 2016)
To determine soil profile and relevant soil characteristics. To analysis liquefaction potential of based on Cyclic Stress Ratio (CSR) and Cyclic Resistance Ratio (CRR) and to make sure the liquefaction susceptibility. To develop liquefaction severity map of the selected study area.